A method for preparing a continuous silicon nitride flexible belt with a skin-core structure
By depositing dopamine and binding nanofibers on the surface of silicon nitride fibers, combining electrospinning and surface treatment technology, a continuous silicon nitride flexible belt is formed in the skin core structure, which solves the damage and sizing of the fibers during the braiding process. Problem, the wovenability and wear resistance of the fiber are improved.
Patent Information
- Application Number
- CN202411281159.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-13
Smart Images

Figure CN118792772B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicon nitride flexible belts, and in particular to a method for preparing a continuous silicon nitride flexible belt with a skin-core structure. Background Art
[0002] Ceramic-based composites are widely used in aerospace, automotive, energy, marine engineering and other fields due to their advantages of high temperature resistance, low density, high hardness and high toughness. Silicon nitride fiber, as a high-performance ceramic fiber, has high specific strength and specific modulus, excellent mechanical properties at room temperature and high temperature, low thermal expansion coefficient, excellent thermal shock resistance, oxidation resistance and chemical corrosion resistance, etc. It is often used as the matrix of ceramic-based composites. When preparing ceramic-based composites, three-dimensional weaving is usually adopted. In the three-dimensional weaving process, due to the inherent brittleness and poor wear resistance of silicon nitride fiber, repeated friction during reciprocating weaving will cause serious fiber damage, greatly reducing its weavability.
[0003] In order to improve the weavability of fibers, a sizing treatment method is usually used. However, during the sizing process of silicon nitride fibers, it is difficult for the surface of the silicon nitride fibers to be fully covered and penetrated by the sizing agent, resulting in a weak bond between the sizing agent and the silicon nitride fibers, making it difficult to form a uniform coating layer, thereby affecting the weavability of the silicon nitride fibers.
[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0005] The technical task of the present invention is to address the above shortcomings and provide a method for preparing a continuous silicon nitride flexible belt with a skin-core structure, by depositing polydopamine on the surface of the silicon nitride fiber to increase the surface roughness of the silicon nitride fiber, and bundling nanofibers on the surface of the silicon nitride fiber, and then surface treating the silicon nitride fibers bundled with the nanofibers, thereby improving the weavability of the silicon nitride fiber.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a continuous silicon nitride flexible belt with a skin-core structure, comprising:
[0008] S10, obtaining nanofibers by electrospinning, and bundling the nanofibers on the surface of the silicon nitride fibers to obtain a flexible tape precursor;
[0009] S20, performing surface treatment on the flexible tape precursor to obtain a continuous silicon nitride flexible tape with a skin-core structure.
[0010] Furthermore, before step S10, the method further includes pre-treating the silicon nitride fiber: continuously immersing the silicon nitride fiber in a dopamine hydrochloride solution, and drying the immersed silicon nitride fiber.
[0011] Further, step S10 includes:
[0012] S11, dissolving a spinnable polymer in a spinning solvent, stirring vigorously and then standing until bubbles in the solution completely disappear, to obtain a spinning solution;
[0013] S12, using the spinning solution to form nanofibers by electrospinning;
[0014] S13, the nanofibers are deposited between the electrospinning receiving device and the silicon nitride fibers; wherein the receiving device is a hollow structure with an open bottom, and the silicon nitride fibers pass through the receiving device;
[0015] S14, the receiving device rotates with the straight line where the silicon nitride fiber is located as the central axis, and the silicon nitride fiber moves unidirectionally at a uniform speed in the direction of the central axis. The nanofibers are bundled on the surface of the silicon nitride fiber under the rotation of the receiving device and the relative movement of the silicon nitride fiber, thereby obtaining a flexible belt precursor.
[0016] Furthermore, in step S11, the spinnable polymer includes but is not limited to one or more of polyurethane, polyvinylidene fluoride, and polyvinyl formal.
[0017] Furthermore, in step S20, the surface treatment is to continuously immerse the flexible belt precursor in a polytetrafluoroethylene solution with a concentration of 5%-20% for 5s-20s, and dry at 150°C for 20s.
[0018] Furthermore, in step S20, the surface treatment is to continuously immerse the flexible tape precursor in a glutaraldehyde solution, the concentration of the glutaraldehyde solution is 20%, the temperature of the glutaraldehyde solution is 35°C, the immersion time is 100s, and the drying is carried out at 100°C for 20s.
[0019] Further, in step S11, the spinnable polymer is polyurethane and polyurethane hot-melt powder, and the mass ratio of polyurethane to hot-melt polyurethane is 7:5;
[0020] In step S20, the surface treatment is to subject the flexible tape precursor to a heat shrink treatment; wherein the heat shrink treatment temperature is 120°C-150°C, and the time is 20s.
[0021] Furthermore, the concentration of dopamine hydrochloride is 0.5 g / L, the immersion time is 2 min, the drying temperature is 50° C., and the drying time is 10 min.
[0022] Further, in step S14, the receiving device rotates at a speed of 200 rad / min, and the silicon nitride fiber moves at a unidirectional uniform speed of 1.0-1.8 m / min.
[0023] Further, in step S11, the stirring temperature is 45° C., the stirring time is 2 hours, the spinning solvent is a mixed solution of N,N-dimethylformamide and tetrahydrofuran, and the concentration of the spinnable polymer in the spinning solution is 12%;
[0024] In step S12, the injection angle of the electrospinning is 30° with the horizontal, the receiving distance is 10-15 cm, the injection speed is 1.5-3 ml / h, and the positive and negative voltages are both 8 kV.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The present invention solves the problem that silicon nitride fibers are easily worn during the weaving process by bundling nanofibers on the surface of silicon nitride fibers. It has the advantages of using nanofibers to coat silicon nitride fibers and reducing the wear of silicon nitride fibers.
[0027] 2. The present invention obtains nanofibers by using electrospinning technology, thereby solving the problems of low production efficiency and low controllability of nanofibers, and has the advantages of controllable parameter conditions and material diversity;
[0028] 3. The present invention solves the problem that the nanofibers after bundling are relatively fluffy and the nanofibers are easily peeled off from the silicon nitride fibers after surface friction by surface treatment of the silicon nitride fibers after bundling the nanofibers. It has the advantages of tightening the nanofibers and improving the bundling rate and breaking strength of the flexible belt.
[0029] 4. The present invention performs surface treatment by physical coating, chemical cross-linking and filling with heat shrinkable materials, which has the advantage of being able to select a suitable surface treatment method according to demand;
[0030] 5. The present invention solves the problem of smooth surface of silicon nitride fiber and loose fibers by depositing polydopamine on the surface of silicon nitride fiber, which has the advantages of increasing the surface roughness and cohesion of silicon nitride fiber and adding anchor points for subsequent bundling treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 It is a schematic diagram of the process of the present invention;
[0033] Figure 2 is an electron microscope image of the silicon nitride fiber of the present invention;
[0034] Figure 3 This is an electron microscope image of the silicon nitride fiber after pretreatment of the present invention;
[0035] Figure 4 This is an electron microscope image of a continuous silicon nitride flexible belt with a skin-core structure according to Example 1 of the present invention;
[0036] Figure 5 This is a microscopic electron microscope image of a continuous silicon nitride flexible belt with a skin-core structure according to Example 1 of the present invention;
[0037] Figure 6 This is an electron microscope image of a continuous silicon nitride flexible belt with a skin-core structure according to Example 2 of the present invention;
[0038] Figure 7 This is an electron microscope image of a continuous silicon nitride flexible belt with a skin-core structure according to Example 3 of the present invention;
[0039] Figure 8 This is an electron microscope image of a continuous silicon nitride flexible belt with a skin-core structure according to Example 4 of the present invention;
[0040] Fig. 9 This is an electron microscope image of a continuous silicon nitride flexible belt with a skin-core structure according to Example 5 of the present invention;
[0041] Fig.10 This is an electron microscope image of a continuous silicon nitride flexible belt with a skin-core structure according to Example 6 of the present invention;
[0042] Fig.11 This is an electron microscope image of a continuous silicon nitride flexible belt with a skin-core structure according to Example 7 of the present invention;
[0043] Fig.12 This is a microscopic electron microscope image of a continuous silicon nitride flexible belt with a skin-core structure according to Example 7 of the present invention;
[0044] Fig.13 This is an electron microscope image of a continuous silicon nitride flexible belt with a skin-core structure according to Example 8 of the present invention;
[0045] Fig.14 This is an electron microscope image of a continuous silicon nitride flexible belt with a skin-core structure according to Example 9 of the present invention;
[0046] Fig.15 It is a schematic diagram of the electrospinning and nanofiber bundling process of the present invention. DETAILED DESCRIPTION
[0047] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0048] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0049] Embodiment 1:
[0050] Pre-treat the silicon nitride fiber:
[0051] Accurately weigh 1 g of potassium dihydrogen phosphate, 1 g of sodium dihydrogen phosphate and 0.5 g of ammonium persulfate and dissolve them in deionized water to obtain a buffer solution. Use 0.1 mol / L sodium hydroxide solution to adjust the pH value of the buffer solution to 8.5. Dissolve dopamine hydrochloride in the buffer solution. The concentration of dopamine hydrochloride is 0.5 g / L.
[0052] The silicon nitride fiber is continuously immersed in the dopamine hydrochloride solution. Specifically, starting from one end of the silicon nitride fiber, the silicon nitride fiber is sequentially passed through the groove filled with the dopamine hydrochloride solution to ensure that the silicon nitride fiber in the groove can be immersed in the dopamine hydrochloride solution. The immersion time is 2 minutes. The immersed silicon nitride fiber is passed through a blast drying oven with channels at both ends for drying. The drying temperature is 50°C and the drying time is 10 minutes.
[0053] In this embodiment, dopamine hydrochloride is subjected to oxidation reaction and polymerization reaction to obtain polydopamine, which is deposited on the surface of silicon nitride fiber, thereby increasing the surface roughness of silicon nitride fiber, thereby providing an anchor point for subsequent bundling. It is understandable that if silicon nitride fiber has been pretreated before leaving the factory, and the surface roughness of silicon nitride fiber meets the bundling requirements, the silicon nitride fiber pretreatment step can be omitted.
[0054] In this embodiment, the dipping time and the drying time are adjusted by adjusting the speed of the silicon nitride fiber.
[0055] The dried silicon nitride fibers are collected to obtain silicon nitride fibers.
[0056] For electron micrographs of silicon nitride fiber and silicon nitride fiber after pretreatment, please refer to the attached Figure 2-3 .
[0057] Step S10: obtaining nanofibers by electrospinning, and bundling the nanofibers on the surface of the silicon nitride fibers to obtain a flexible tape precursor.
[0058] S11. Accurately weigh 0.7 g of polyurethane and 0.5 g of polyvinylidene fluoride, add them into 3.5 g of N,N-dimethylformamide and 5.3 g of tetrahydrofuran, and vigorously stir at 45° C. for 2 h to obtain a uniform spinning solution.
[0059] S12. Turn on the electrospinning instrument, inject the spinning solution into the injection device, set the injection angle to 30° with the horizontal angle, adjust the receiving distance to 10cm-15cm, the injection speed to 3ml / h, and the positive and negative voltages to 8kV to form nanofibers through electrospinning.
[0060] S13, the nanofibers are deposited between a receiving device of an electrospinning instrument and the silicon nitride fibers; wherein the receiving device is a hollow structure with an open bottom, and the silicon nitride fibers pass through the receiving device;
[0061] In this embodiment, the receiving device of the electrospinning instrument is configured as an inverted bowl-shaped structure with an opening at the bottom of the bowl. The silicon nitride fibers vertically pass through the receiving device, and the nanofibers formed by electrospinning are overlapped between the receiving device and the silicon nitride fibers.
[0062] S14, the receiving device rotates with the straight line where the silicon nitride fiber is located as the central axis, the silicon nitride fiber moves unidirectionally at a uniform speed in the direction of the central axis, and the nanofibers are bound to the surface of the silicon nitride fiber under the rotation of the receiving device and the relative movement of the silicon nitride fiber, thereby obtaining a flexible belt precursor;
[0063] In this embodiment, please refer to the attached Fig.15 The receiving device rotates clockwise with the straight line where the silicon nitride fiber is located as the central axis, and the silicon nitride fiber moves vertically downward at a uniform speed. Through the rotation of the receiving device and the relative movement of the silicon nitride fiber, an umbrella-like structure is formed, so that the nanofibers are bundled on the surface of the silicon nitride fiber. The rotation speed of the receiving device is 200 rad / min, and the unidirectional uniform motion speed of the silicon nitride fiber is 1.8 m / min.
[0064] The bundled silicon nitride fibers are collected to form a flexible tape precursor.
[0065] Step S20: performing surface treatment on the flexible tape precursor to obtain a continuous silicon nitride flexible tape with a skin-core structure.
[0066] Specifically, the flexible belt precursor is sequentially passed through a groove containing a polytetrafluoroethylene solution, the concentration of the polytetrafluoroethylene solution is 5%, the immersion time is 5 seconds, and the impregnated flexible belt precursor is passed into a blast drying oven with channels at both ends, and dried at 150° C. for 20 seconds;
[0067] The flexible tape precursor after surface treatment is collected to obtain a continuous silicon nitride flexible tape with a skin-core structure.
[0068] Embodiment 2:
[0069] In step S14, the unidirectional uniform motion speed of the silicon nitride fiber is 1.0 m / min, and other conditions and steps are the same as those in Example 1 and are not described herein.
[0070] Embodiment 3:
[0071] In step S20, the flexible tape precursor is immersed in the polytetrafluoroethylene solution for 20 seconds. Other conditions and steps are the same as those in Example 1 and are not described in detail here.
[0072] Embodiment 4:
[0073] In step S20, the concentration of the polytetrafluoroethylene solution is 20%, and other conditions and steps are the same as those in Example 1 and are not described herein.
[0074] Examples 1-4 are all about using physical coating method to treat the surface of the flexible tape precursor. Please refer to the attached electron microscope images. Figure 4-8 .
[0075] Attached Figure 4 It can be seen that nanofibers and polytetrafluoroethylene can be evenly coated on silicon nitride fibers, and the bundling of the continuous silicon nitride flexible tape with skin-core structure is greatly improved compared with silicon nitride fibers;
[0076] From the attached Figure 5 It can be seen from the electron microscope image that the polytetrafluoroethylene on the surface of the skin-core continuous silicon nitride flexible belt effectively fills the three-dimensional structure of the nanofibers;
[0077] Attached Figure 6 It can be seen that due to the slow unidirectional uniform movement speed of silicon nitride fiber, the diameter of the continuous silicon nitride flexible belt with skin-core structure increases, the bundling rate of the continuous silicon nitride flexible belt with skin-core structure decreases, and the wear resistance is improved;
[0078] Attached Figure 7 It can be seen that the coating amount of polytetrafluoroethylene has increased, the surface of the continuous silicon nitride flexible belt with skin-core structure has become smoother, the wear resistance of the fiber has improved, the friction coefficient has decreased, but the quality of the fiber has increased significantly;
[0079] Attached Figure 8 It can be seen that at a 20% polytetrafluoroethylene concentration, the time is 5s to achieve the desired adhesion. Figure 7 The surface of the continuous silicon nitride flexible belt with skin-core structure is smooth, the wear resistance of the fiber is improved, and the friction coefficient is reduced, which shows that controlling the coating amount of polytetrafluoroethylene can control both the coating time and the polytetrafluoroethylene concentration.
[0080] Embodiment 5:
[0081] In step S11, 0.7 g of polyurethane and 0.5 g of polyvinyl formal are accurately weighed and added to 3.5 g of N,N-dimethylformamide and 5.3 g of tetrahydrofuran;
[0082] In step S12, the injection speed is 1.5 ml / h, and the positive and negative voltages are both 9 kV;
[0083] In step S20, the flexible belt precursor is sequentially passed through a groove containing a glutaraldehyde solution, the concentration of the glutaraldehyde solution is 20%, the temperature of the glutaraldehyde solution is 35°C, the immersion time is 100s, and the impregnated flexible belt precursor is passed into a blast drying oven with two end channels, and dried at 100°C for 20s;
[0084] The other conditions and steps are the same as those in Example 1 and will not be described in detail here.
[0085] Embodiment 6:
[0086] In step S14, the unidirectional uniform motion speed of the silicon nitride fiber is 1.0 m / min, and other conditions and steps are the same as those in Example 5 and are not described herein.
[0087] Examples 5-6 are all about using chemical crosslinking method to treat the surface of the flexible belt precursor. Figure 9-10 .
[0088] Attached Fig. 9 It can be seen that the fiber layer of the skin-core continuous silicon nitride flexible belt is relatively thin. After passing through the glutaraldehyde solution, the fluffy type of the nanofiber disappears, which has a good cross-linking effect, making the skin-core continuous silicon nitride flexible belt have good bundling properties, effectively reducing the friction coefficient and wear of the fiber;
[0089] Attached Fig.10 It can be seen that the fiber layer of the continuous silicon nitride flexible belt with skin-core structure is thicker. After passing through the glutaraldehyde solution, the fluffy type of the nanofibers also disappears. The thicker nanofiber layer helps to reduce fiber wear.
[0090] Embodiment 7:
[0091] In step S11, 0.7 g of polyurethane and 0.5 g of polyurethane hot melt powder are accurately weighed and added to 3.5 g of N,N-dimethylformamide and 5.3 g of tetrahydrofuran;
[0092] In step S12, the injection speed is 1.5 ml / h;
[0093] Step S20 is to directly pass the flexible tape precursor into a blast drying oven with channels at both ends for heat shrinkage treatment at a temperature of 150° C. for a time of 20 seconds;
[0094] The other conditions and steps are the same as those in Example 1 and will not be described in detail here.
[0095] Embodiment 8:
[0096] In step S14, the unidirectional uniform motion speed of the silicon nitride fiber is 1.0 m / min, and other conditions and steps are the same as those in Example 7 and are not described herein.
[0097] Embodiment 9:
[0098] In step S14, the silicon nitride fiber moves at a uniform unidirectional speed of 1.0 m / min;
[0099] In step S20, the heat shrinkage treatment temperature is 120°C;
[0100] The other conditions and steps are the same as those in Example 7 and will not be described in detail here.
[0101] Examples 7-9 are all about filling heat shrinkable materials to treat the surface of the flexible belt precursor. The electron microscope images are shown in the attached Figure 11-14 .
[0102] Attached Figure 11-12 It can be seen that the nanofibers shrink greatly when subjected to high heat of 150°C, which greatly improves the bundling of silicon nitride fibers, and the breaking strength of the continuous silicon nitride flexible belt with skin-core structure after molding is greatly improved; from the microscopic electron microscope image, we can see that the nanofibers on the surface of silicon nitride are coated on the silicon nitride fibers in a film-like manner, and this form is conducive to reducing the wear and friction coefficient of silicon nitride;
[0103] Attached Fig.13 It can be seen that the diameter of the continuous silicon nitride flexible belt with skin-core structure has increased, the bundling rate has decreased, but the nanofiber layer is thicker and the wear resistance is improved;
[0104] Attached Fig.14 It can be seen that the nanofibers on the surface of the skin-core structured continuous silicon nitride flexible belt are relatively thin, and the fiber shrinkage is limited after being subjected to low heat at 120°C, and the bundling of silicon nitride is relatively low. However, under this condition, it is conducive to the mass production of the skin-core structured continuous silicon nitride flexible belt.
[0105] Test indicators and test standards of Examples 1-9 and silicon nitride fibers:
[0106] (1) Single yarn breaking strength test standard
[0107] The breaking strength test refers to GB / T 3362-2017 "Test method for tensile properties of carbon fiber multifilaments". The two ends of the sample are fixed with reinforcement plates. The effective length of the sample is 150 mm, the pre-tension is 0.5 N, and the tensile test rate is 50 mm / min. Each group of experiments is tested for 10 groups and the average value is taken.
[0108] (2) Single yarn hook strength test standard
[0109] The hook strength test refers to GB / T 14344-2008 "Test method for tensile properties of chemical fiber filaments". Two single yarns are folded in half, the ends are put together and placed in the fiber tensile fixture. The effective length of the sample is 500 mm, the pre-tension is 0.1N, the loading speed is 50 mm / min, and each group of experiments is tested 10 times and the average value is taken.
[0110] (3) Single yarn bundling test standard
[0111] First, cut a long fiber sample, pass the fiber around a solid stick in turn, and hang 50g weights at both ends of the fiber. Measure the unfolded width of the fiber bundle on the solid stick, and calculate its change with the original yarn width. The greater the positive change rate, the better the bundling. Each group of fibers is tested 10 times and the average value is calculated.
[0112] (4) Friction coefficient
[0113] The friction test was carried out using the UMT-TriboLab friction and wear tester with a low-speed linear reciprocating motion module and electromagnetic sensor. The reciprocating motion of the steel buckle was set to 4 mm and the normal load was 0.3 N.
[0114] The test results of Examples 1-9 and silicon nitride fibers are shown in Table 1.
[0115] The main factors affecting the performance of silicon nitride fiber preforms include the breaking strength, hook strength, bundling rate and friction performance of silicon nitride fibers. From Table 1, it can be seen that the breaking strength, hook strength and bundling of the continuous silicon nitride flexible tapes obtained by the three methods have been significantly improved compared with silicon nitride fibers, and the friction coefficient of silicon nitride fibers has also been reduced.
[0116] Among them, in Examples 1-4, the continuous silicon nitride flexible belt has an increase in breaking strength of 2.3%-15.5% compared to silicon nitride fiber, an increase in hooking strength of 49.5%-90.9%, an increase in bundling rate of 38.6%-69.8%, and a decrease in friction coefficient of 40%-60%;
[0117] In Examples 5-6, the breaking strength of the continuous silicon nitride flexible belt is increased by 4.8%-17.2% compared to silicon nitride fiber, the hooking strength is increased by 69.4%-76.6%, the bundling rate is increased by 47.3%-50.6%, and the friction coefficient is reduced by 42.5%-55%.
[0118] In Examples 7-9, the breaking strength of the continuous silicon nitride flexible belt is increased by 3.3%-12.2% compared to silicon nitride fiber, the hooking strength is increased by 40.5%-85.6%, the bundling rate is increased by 37.6%-89.6%, and the friction coefficient is reduced by 40%-52.5%.
[0119] Table 1 Test results of Examples 1-9 and silicon nitride fibers
[0120]
[0121] Through the above specific implementations, those skilled in the art can easily implement the present invention. However, it should be understood that the present invention is not limited to the above specific implementations. On the basis of the disclosed implementations, those skilled in the art can arbitrarily combine different technical features to achieve different technical solutions.
Claims
1. A method for preparing a continuous silicon nitride flexible belt with a skin-core structure, characterized in that: include: S10, obtaining nanofibers by electrospinning, and bundling the nanofibers on the surface of silicon nitride fibers to obtain a flexible tape precursor; S20, performing surface treatment on the flexible tape precursor to obtain a continuous silicon nitride flexible tape with a skin-core structure; Before step S10, the silicon nitride fiber is also pre-treated: the silicon nitride fiber is continuously immersed in a dopamine hydrochloride solution, and the immersed silicon nitride fiber is dried.
2. The method for preparing a skin-core continuous silicon nitride flexible belt according to claim 1, characterized in that: Step S10 includes: S11, dissolving a spinnable polymer in a spinning solvent, stirring vigorously and then standing until bubbles in the solution completely disappear, to obtain a spinning solution; S12, using the spinning solution to form nanofibers by electrospinning; S13, the nanofibers are deposited between the electrospinning receiving device and the silicon nitride fibers; wherein the receiving device is a hollow structure with an open bottom, and the silicon nitride fibers pass through the receiving device; S14, the receiving device rotates with the straight line where the silicon nitride fiber is located as the central axis, and the silicon nitride fiber moves unidirectionally at a uniform speed in the direction of the central axis. The nanofibers are bundled on the surface of the silicon nitride fiber under the rotation of the receiving device and the relative movement of the silicon nitride fiber, thereby obtaining a flexible belt precursor.
3. The method for preparing a skin-core continuous silicon nitride flexible belt according to claim 2, characterized in that: In step S11, the spinnable polymer includes one or more of polyurethane, polyvinylidene fluoride, and polyvinyl formal.
4. The method for preparing a continuous silicon nitride flexible belt with a skin-core structure according to claim 3, characterized in that: In step S20, the surface treatment is to continuously immerse the flexible belt precursor in a polytetrafluoroethylene solution with a concentration of 5%-20% for 5s-20s, and dry at 150°C for 20s.
5. The method for preparing a skin-core continuous silicon nitride flexible belt according to claim 3, characterized in that: In step S20, the surface treatment is to continuously immerse the flexible tape precursor in a glutaraldehyde solution with a concentration of 20%, a temperature of 35°C, an immersion time of 100s, and drying at 100°C for 20s.
6. The method for preparing a skin-core continuous silicon nitride flexible belt according to claim 2, characterized in that: In step S11, the spinnable polymer is polyurethane and polyurethane hot-melt powder, and the mass ratio of polyurethane to hot-melt polyurethane is 7:5; In step S20, the surface treatment is to subject the flexible tape precursor to a heat shrink treatment; wherein the heat shrink treatment temperature is 120° C.-150° C., and the time is 20 seconds.
7. The method for preparing a skin-core continuous silicon nitride flexible belt according to claim 1, characterized in that: The concentration of dopamine hydrochloride is 0.5 g / L, the immersion time is 2 min, the drying temperature is 50° C., and the drying time is 10 min.
8. The method for preparing a skin-core continuous silicon nitride flexible belt according to claim 2, characterized in that: In step S14, the receiving device rotates at a speed of 200 rad / min, and the silicon nitride fiber moves at a unidirectional uniform speed of 1.0 m / min-1.8 m / min.
9. The method for preparing a skin-core continuous silicon nitride flexible belt according to claim 2, characterized in that: In step S11, the stirring temperature is 45° C., the stirring time is 2 hours, the spinning solvent is a mixed solution of N,N-dimethylformamide and tetrahydrofuran, and the concentration of the spinnable polymer in the spinning solution is 12%; In step S12, the injection angle of the electrospinning is 30° with the horizontal, the receiving distance is 10 cm-15 cm, the injection speed is 1.5 ml / h-3 ml / h, and the positive and negative voltages are both 8 kV.
Citation Information
Patent Citations
Stretchable multi-mode sensor based on nanofiber core spun yarn and preparation method thereof
CN109355715A
Continuous silicon nitride fiber-reinforced resin-based composite wire and preparation method thereof
CN110305464A